Graphene quantum dots modification of yolk-shell Co3O4@CuO microspheres for boosted lithium storage performance - Wu, Minghong; Chen, Hengqiao; Lv, Li-Ping; Wang, Yong (Chemical engineering journal (Lausanne, Switzerland : 1996), 2019)
[Display omitted] •Co3O4@CuO microspheres are prepared and modified with graphene quantum dots (GQDs).•The Co3O4@CuO@GQDs exhibits a unique yolk-shell and mesoporous structure.•The modification of GQDs boosts the lithium storage behavior for Co3O4@CuO. In this report, we present the synthesis of yolk-shell Co3O4@CuO microspheres followed with the surface modification of carboxyl-functionalized graphene quantum dots (donated as Co3O4@CuO@GQDs) and investigate their lithium storage properties. Derived from metal-organic frameworks (MOFs), the obtained yolk-shell Co3O4@CuO microspheres exhibit well-defined microstructure and high porosities. The yolk-shell Co3O4@CuO structure is designed to adapt the stepwise lithium insertion mechanism (first in CuO shell and then in Co3O4 core). In addition, the GQDs decorated on the surface of Co3O4@CuO microspheres not only provides larger specific surface area, more active sites and enhanced electronic conductivity, but also works as a buffer to alleviate the volume expansion and a reservoir for electrolyte molecules to improve the ionic conductivity. Furthermore, the –COOH groups from GQDs exhibits good hydrophilicity which is supposed to be useful for the combination of GQDs with Co3O4@CuO and also shows strong affinity to Li+. Based on the above merits from the structural and compositional design, the Co3O4@CuO@GQDs anode displays enhanced cyclability and superior lithium storage performance. Specifically, compared to the bald Co3O4@CuO microspheres without GQDs which suffer from a severe capacity decline with an inferior capacity of 414 mAh g−1 after 200 cycles, the Co3O4@CuO@GQDs anode displays an initial specific capacity of 816 mAh g−1 and a high reversible charge capacity of 1054 mAh g−1 after 200 cycles at 0.1 A g−1.